Promoting Dental Check-up for Pregnant Women - Tasyakuranti, Maulidina Nabilah; Linati, Pramesti Audigita; Azkiyah, Farah; Erzaligina, Delavia Faniga; Fajarrudin, Fajarrudin; Lazuardi, Daniyal; Pratiwi, Hasnah Diah; Pitaloka, Pradipta; Putri, Nilna Nur Putri, Nur; Tjahyono, Natalia; Virgianti, Inggit Dwi; Setijanto, R. Darmawan (Faculty of Dental Medicine Universitas Airlangga, 2019)
Background: Dupak Public Health Center is one of the public health service facilities in Surabaya that provides integrated dental and oral health services. Dupak Public Health Center covers Dupak District area. Only 8.2% out of 366 pregnant women visited the dental poly from April 2017–April 2018. An epidemiological study reported that dental visitation in pregnant women in the Dupak Public Health Center was still very low. Lower knowledge levels of pregnant women about dental and oral health caused the low dental visitation in the dental poly. An intervention was needed to change the negative behavior related to dental and oral health, especially in pregnant women. Purpose: To increase the dental visitation of pregnant women in the dental poly of the Dupak Public Health Center. Methods: The program adopted the health education strategy with a group approach. The group means cadres of pregnant women. Pregnant women learned about dental and oral health during pregnancy. Results: Eight pregnant women were attending the invitation. The pretest result showed that 71.60% of pregnant women had answered questions correctly, and the post-test result showed that 88.75% of pregnant women had answered the questions correctly. Conclusion: This program is effective to increase the knowledge of pregnancy woman that will lead to dental visitation.